1998
DOI: 10.1007/s004420050621
|View full text |Cite
|
Sign up to set email alerts
|

Daphnid morphology deters fish predators

Abstract: Spine and helmet production in zooplankton are thought to provide protection from invertebrate rather than vertebrate predators. We examined selectivity for Daphnia lumholtzi, a species that exhibits extreme cyclomorphosis with a large helmet and long tail spine (total length can exceed 5 mm), by juvenile bluegill (15-80 mm) in the laboratory and field. Bluegill consumed more D. pulex than D. lumholtzi when the species were presented alone. When the daphnids were offered together in equal numbers, bluegill sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 44 publications
1
61
1
2
Order By: Relevance
“…Resistance to predation might be a determinant factor in the successful invasion of this species because the carapace spine and helmet of D. lumholtzi protect against invertebrate predation (Kolar & Wahl, 1998), although this is still a matter of speculation because the real protective potential of such structures is not well known (Dzialowski et al, 2000). Many invaders are successful because, besides resistance to predation (Crawley, 1986), either native competitors are ineffective or other species do not take advantage of existing opportunities.…”
Section: )mentioning
confidence: 99%
“…Resistance to predation might be a determinant factor in the successful invasion of this species because the carapace spine and helmet of D. lumholtzi protect against invertebrate predation (Kolar & Wahl, 1998), although this is still a matter of speculation because the real protective potential of such structures is not well known (Dzialowski et al, 2000). Many invaders are successful because, besides resistance to predation (Crawley, 1986), either native competitors are ineffective or other species do not take advantage of existing opportunities.…”
Section: )mentioning
confidence: 99%
“…This length compares to 2-3.5 cm for bluegill sunfish used by Swaffar and O'Brien (1996), and 1-8 cm for bluegills used by Kolar and Wahl (1998). Kolar and Wahl (1998) found that bluegills with a length of up to 5 cm had difficulty in handling D. lumholtzi and learned to reject them. In contrast, bluegills with a length above 5 cm were able to ingest D. lumholtzi, although less efficiently than undefended D. pulex.…”
Section: Study Organismsmentioning
confidence: 82%
“…Some other clones are permanently defended: they carry these defenses even in the absence of predator cues. Swaffar and O'Brien (1996) and Kolar and Wahl (1998) conducted feeding experiments with bluegill sunfish (Le-pomis macrochirus) on D. lumholtzi compared to other Daphnia species. They showed that the spines of D. lumholtzi make it difficult for juvenile sunfish to consume these defended Daphnia and strongly increase their handling time.…”
Section: Introductionmentioning
confidence: 99%
“…This concept suggests that the promotion of efficient planktonic herbivores through decreased biomass of planktivores by piscivores can reduce the biomass of phytoplankton. This general pattern can be modified by altered life histories or other interactions among particular species such as defence mechanisms in prey (Jeffries, 1988;Kolar and Wahl, 1998;Straile and Halbich, 2000). These findings are widely used during food web manipulation with the ultimate goal to improve water quality management (i.e., biomanipulation techniques) (Berg et al, 1997;Beklioglu, 1999;Ha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%